1991
DOI: 10.1159/000461353
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Intravenous IgG for the Treatment of Severe Rhesus Alloimmunization

Abstract: The value of intravenous immunoglobulin (IVIG) in the treatment of 24 severely Rh-sensitized pregnant women was studied. IVIG was infused at a daily dose of 0.4 g/kg maternal body weight for 4-5 consecutive days, and was administered again 15-21 days later until delivery, depending on the evolution of the hemolytic disease. Our population was divided into 3 groups according to the time of onset of therapy: group 1 (n = 8), before 20 weeks’ gestation; group 2 (n = 7), 20-28 weeks, and group 3 (n = 9), after 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…IVIG treatment caused a significant decline in anti-D titers and hemolysis rate and even averted invasive IUT in this severely affected group if started before 28 weeks' gestation. Nevertheless, they concluded that for hydropic fetuses and for fetuses with advanced fetal anemia, IUT is inevitable [90]. In a retrospective study of the same group, patients receiving IVIG before 20 weeks had significantly less hydropic fetuses and a lower fetal mortality rate compared to patients treated with IUT alone [84].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
See 1 more Smart Citation
“…IVIG treatment caused a significant decline in anti-D titers and hemolysis rate and even averted invasive IUT in this severely affected group if started before 28 weeks' gestation. Nevertheless, they concluded that for hydropic fetuses and for fetuses with advanced fetal anemia, IUT is inevitable [90]. In a retrospective study of the same group, patients receiving IVIG before 20 weeks had significantly less hydropic fetuses and a lower fetal mortality rate compared to patients treated with IUT alone [84].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…A truly evidence-based noninvasive approach to further reduce fetal loss rates is however not yet available. Nevertheless, the use of intravenous immunoglobulins to postpone these hazardous early IUTs, potentially combined with TPE, shows promising results in case series and single center case-control studies [84,90]. Therapeutic plasma exchange alone seems unable to create similar results.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Margulies et al [43] conducted the largest prospective series to date in which 24 severely Rh-sensitized pregnant women were treated with IVIG alone until delivery and demonstrated that IVIG use should be initiated before 28 weeks or before the appearence of hydrops. In addition, Voto et al [85] demonstrated the predominance of the combined treatment with IVIG and IUT over IUT alone, as in the fi rst group, severe fetal anemia was less common and fetal mortality was reduced by 36 % compared with the second group.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…Unfortunately, the dosage of IVIg administered to the fetus in this study was too low to expect macrophage blocking. The largest case study comprising 24 severely Rh-sensitized pregnant women found a reduction of in utero hemolysis and fetal death when maternal IVIg treatment was started before the 28th week in non-hydropic fetuses (97). In 3 randomized trials (98-100) administration of IVIg after delivery to neonates with rhesus hemolytic disease significantly reduced the need for exchange transfusions.…”
Section: Miscellaneousmentioning
confidence: 99%
“…** Non-randomized prospective series in which at least 2 patients were described. ll In the study of Margulies (97). it is not possible to exactly identify the responders to IVlg.…”
mentioning
confidence: 99%